2018
DOI: 10.18332/tpc/90857
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary health care in assessing and preventing health risk factors of adolescents in Georgia

Abstract: is an open access, peer-reviewed online journal that encompasses all aspects of tobacco use, prevention and cessation that can promote a tobacco free society. The aim of the journal is to foster, promote and disseminate research involving tobacco use, prevention, policy implementation at a regional, national or international level, disease development-progression related to tobacco use, tobacco use impact from the cellular to the international level and finally the treatment of tobacco attributable disease thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Prevention-centric approaches are missing in PHC in all CIS countries (Luck et al, 2014). The state system is still promoting disease management at PHC and forgetting the key role of disease prevention and early detection, which is an essential component of PHC (Dzhakeli et al, 2009;Efremov, 2011;Sharman, 2014;Mirzikashvili and Baramidze, 2017). A study on the NCD-related risk factors conducted in 27 countries, including CIS countries, confirmed that addressing the risk factors plays a key role in preventing most of NCDs (Kotseva, 2019).…”
Section: Service Deliverymentioning
confidence: 99%
“…Prevention-centric approaches are missing in PHC in all CIS countries (Luck et al, 2014). The state system is still promoting disease management at PHC and forgetting the key role of disease prevention and early detection, which is an essential component of PHC (Dzhakeli et al, 2009;Efremov, 2011;Sharman, 2014;Mirzikashvili and Baramidze, 2017). A study on the NCD-related risk factors conducted in 27 countries, including CIS countries, confirmed that addressing the risk factors plays a key role in preventing most of NCDs (Kotseva, 2019).…”
Section: Service Deliverymentioning
confidence: 99%